AUTOMATIC FARMING SYSTEM - Adhav, Kailas; Wankhede, Abhilesh (International Journal of Students’ Research in Technology & Management, 2015)
Since Olden times man has been cultivating and depending heavily on the plant and crops to arrange for the staple food. To do this he had to toil and severe with labor. As the technology advances people wish for more and more comfort, reliability and fast operation. India is the farmerâ€™s country and major part of the revenue is generated out of the agriculture industry Keeping the above ideology in mindÂ this project propose to design a unit with following features: 1.ploughing 2.seedsowing 3.cutting etc. This studyÂ develop an Energy Saving Automatic Farming System with two unit User unit (remote control) & Solar Powered Tractor Unit. From user unit i.e. Wireless remote it gives instruction to the tractor unit to perform various task such as plugging, seed sowing, cutting etc The required power supply for performing various task is obtained from solar panel using tracking and trapping system to obtain maximum solar energy. For automation of tractor unit it uses memory mapping which will be performed by microcontroller in embedded c using Kiel software.